An electrocaloric device demonstrator for solid-state cooling - Chukka, Rami (2013)
A prototype device was designed to demonstrate electrocaloric cooling of Pb(Mg1/3Nb2/3)O3-PbTiO3 70/30 single crystals as active cooling elements. The test section was devised to investigate potential bulk cooling effects of the single-crystal materials under repeated electric-field cycles. Despite the low electrocaloric temperature changes measured by indirect method (Delta Tmax = 2.7K in 240 V), the test materials showed significant cooling rates under optimized device parameters compared to those of natural cooling conditions. It was emphasized that the pulse duration and frequency of the applied electric field play an important role in achieving high cooling rates in electrocaloric cooling devices besides high electrocaloric effects of test materials.